Growth performance and nutrient digestibility of broiler chickens as affected by a novel protease - Vieira, Sergio Luiz; de Freitas, Camila Rodrigues; Horn, Raquel Moreira; Favero, Andre; Kindlein, Liris; Sorbara, Jose Otavio Berti; Umar-Faruk, Murtala (Frontiers in Animal Science, 2023)
Two experiments evaluated the addition of an exogenous sfericase protease in broiler feeds. In experiment 1 (Exp1), 1,848 day-old male chicks were allocated into 84-floor pens with 14 replicates of 22 birds each whereas in experiment 2 (Exp2), 2,100 one-day-old male chicks were allocated in 84-floor pens with 14 replicates of 25 birds each. Conduction was in a completely randomized design. Feeds were formulated with apparent metabolizable energy (AME) and nutrients as usual in commercial integrations. Standard feeds had ideally balanced amino acids (AA) whereas Matrix feeds had a reduction of 6% digestible lysine compared to the Standard. Both Standard and Matrix feeds were supplemented with the sfericase protease at 0, 10,000, and 30,000 New Feed Protease units (NFP)/kg. Standard feeds were formulated with 7% lower AA densities in Exp1 compared to Exp2. No interaction was found between feed and protease in any of the experiments. In Exp1, broilers fed Matrix feeds had lower feed conversion ratios (FCR) between 1 to 35 d of age compared to birds fed the Standard (P < 0.05) whereas protease inclusion at 10,000 and 30,000 NFP/kg led to lower FCR compared to no protease inclusion (P < 0.05). No significant differences were found for protease inclusion in feed intake (FI), body weight gain (BWG), and FCR from all cumulative periods (1 to 21 d, 1 to 35 d, and 1 to 42 d; P > 0.05) in Exp2. A higher IDCP was significantly found for birds fed Matrix feeds when compared to those fed the Standard (P < 0.05; Exp1). Protease addition of 10,000 and 30,000 NFP/kg led to higher IDM and IDCP (P < 0.05) compared to no addition whereas the protease inclusion of 30,000 had higher IDE compared to broilers fed no protease (P < 0.05). In Exp2, no significant digestibility effects were observed (P > 0.05). Results demonstrated that the novel sfericase protease could be successfully used in corn-soy diets with protein and AA reductions or in feed formulations with usual digestible AA levels to enhance the growth performance of broilers.